A New Supplement to Spiritual Leadership from Spiritual Intelligence Conceptions and Etymologic Research - Michael Hagemann (International School for Social and Business Studies, 2022)
Purpose: This study identifies, compiles and compares different definitions of Spiritual Intelligence to detect common principles, it reviews the historical emergence of the word "spiritual" and proposes a new construct of Spiritual Intelligence. Methodology/approach: A literature review and a systematic creation of principles have been applied. Findings: It has been detected that the original meaning of "spiritual" has not been considered in the existing research. From the original meaning of "spiritual" a new construct for Spiritual Intelligence has been derived and is proposed for further research. Originality/value: The origins of "spiritual" have not been studied before, hence the new construct of Spiritual Intelligence will be the new fundament for further research